Novel assay procedures for the measurement of α‐amylase in weather‐damaged wheat. (27th February 2015) - Cornaggia, Claudio; Ivory, Ruth; Mangan, David; McCleary, Barry V
Abstract: BACKGROUND: The measurement of α ‐amylase (EC 3.2.1.1) in sprout‐damaged grains is a crucial analysis yet a problematic one owing to the typically low α ‐amylase levels in ground wheat samples. A number of standardised methods such as the Falling Number method and the Ceralpha method exist which are routinely used for the assay of α ‐amylase. These methods, however, are either highly substrate‐dependent or lack the required sensitivity to assess sprout damage. RESULTS: Novel colorimetric and fluorometric reagents have been prepared (Amylase HR, Amylase SD, BzCNPG7 reagent and BzMUG7 reagent) for the direct and specific assay of α ‐amylase activity in sprout‐damaged wheat. Assays employing these reagents have been developed and optimised to include a decolourisation step using activated charcoal. When used in a convenient assay format, Amylase SD – containing EtNPG7 (II) as the colorimetric substrate and α ‐glucosidase as the ancillary enzyme – was found to be an excellent reagent for the assessment of sprout damage in wheat with incubation times as short as 5 min. CONCLUSION: The assay using Amylase SD is completely specific for α ‐amylase. The use of the Amylase SD assay represents a sensitive and valid alternative to the traditionally used Falling Number values for the assessment of sprout damage in wheat samples. © 2015 Society of Chemical Industry